2015
DOI: 10.1128/aac.00637-15
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Y319H Substitution in CYP51C Associated with Azole Resistance in Aspergillus flavus

Abstract: cThis study aimed to explore any mutation in the CYP51 gene conferring azole resistance in Aspergillus flavus. Two voriconazoleresistant and 45 voriconazole-susceptible isolates were included in the study. Sequence analysis demonstrated a T1025C nucleotide change in CYP51C, resulting in the Y319H amino acid substitution in one resistant isolate. However, the earlier described T788G mutation in CYP51C conferring voriconazole resistance in A. flavus isolates was present in all isolates, irrespective of their sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 27 publications
3
81
0
Order By: Relevance
“…An MIC value >16 μg/ml was observed for an isolate of A. flavus from Patient 3 (see Results). This result could have been spurious, or may represent a case of azole resistance, which has recently been described in A. flavus isolates 45,46. The R. arrhizus isolate from Patient 10 was found to have an MIC for isavuconazole of >16 μg/ml using both methods, which may represent an R. arrhizus var.…”
mentioning
confidence: 75%
“…An MIC value >16 μg/ml was observed for an isolate of A. flavus from Patient 3 (see Results). This result could have been spurious, or may represent a case of azole resistance, which has recently been described in A. flavus isolates 45,46. The R. arrhizus isolate from Patient 10 was found to have an MIC for isavuconazole of >16 μg/ml using both methods, which may represent an R. arrhizus var.…”
mentioning
confidence: 75%
“…Therefore, one could consider that standard dosing of voriconazole could be used for the successful treatment of infections caused by A. flavus for which MICs are as high as 2 to 4 mg/liter. Alarmingly, azole resistance is now reported in cases of aspergillosis due to A. flavus (16). In countries like India, where A. flavus is the primary fungus causing cerebral or sino-orbital aspergillosis, the situation is far more crucial (4, 6).…”
Section: Discussionmentioning
confidence: 99%
“…This model indicated that the Y319H substitution was located far from the iron porphyrin complex and hence did not have a direct effect on the docking of the azoles at the binding site. Instead this mutation exhibited increased conformational flexibility, probably due to polar nature of histidine which causes interatomic repulsion leading to reduced drug binding affinity (16). A third explanation could be a difference in levels of virulence between susceptible and resistant strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the widespread use of azoles in clinical practice and agriculture, the emergence of triazole resistance in A. fumigatus has become a global public health concern. Moreover, mutations in A. flavus cyp51A (T788G) and cyp51C (Y319H), both associated with increased MICs to voriconazole, have also been reported recently (11).…”
mentioning
confidence: 99%